The Urgency of Supervision Institutions in Implementing Prisoners' Rights as an Effort to Restructure Criminal Execution Laws - Widyawati, Anis; Maskur, Muhammad Azil; Aisy, Rohadhatul; Teeraphan, Papontee; Setyanto, Heru (Jambura Law Review, 2025)
This research explores the protective laws and enforcement of human rights in Indonesian correctional facilities, especially by observing systematic problems in exercising the ruling on prisoners' rights.  This study uses a juridical-empirical method based on analyzing legal sources with additional field research to cover what legal contents advocate for in what contexts more effectively. It analyzes primary legal materials,including relevant legislation and gathers empirical data throughinterviews and direct observations. This approach allows for an enhanced understanding of the interplay between legal theory and practice to evaluate the legal framework of prisoners' rights protection critically. The findings reveal significant legal gaps, particularly regarding the unclear constitutional arrangements regarding the separation of powers in the execution of sentences as well as the protection of prisoners' rights. These issue are notably prevalent in correctional institutions in Central Java, which has been the case that the enforcement mechanism has not been running optimally. The analysis identifies systematic violations of prisoners' rights stemming from structural weaknesses in the legal relationships between correctional institutions, courts, and other law enforcement entities. As outlined in the examination of statutory interpretation and legal principles throughout this study, legislative reform is also necessary to better protect prisoners' rights, particularly concerning clarification of institutional authority and improved oversight mechanisms. These findings highlight the necessity for legal harmonization between human rights standards and correctional practices to increase the integrity of the Indonesian criminal justice system.